Tradisi Lisan Sumur Tua Daerah Labuhan Batu Utara - Fina Mardiana Nasution; Rosmawaty Harahap; Elly Prihasti Wuriyani (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
Oral literature is a form of literature that is usually considered as a hereditary culture orally or by word of mouth. Oral literature can be in the form of folk tales, legends, fairy tales, myths, and others. Folklore is traditional literature because it is the result of works that were born from a group of people who still strongly adhere to traditional cultural values ??(Dharmojo, 1998:21). Traditional literature is sometimes referred to as folklore and is considered a common property. It grew from a strong collective consciousness in the old society. Danandjaja (1986:2) suggests that folklore is part of a collective culture that is spread and passed down from generation to generation, among any kind of collective, traditionally in different versions, both in oral form and examples accompanied by gestures or reminder aids. mnemonic devices). From this opinion, it can be concluded that folklore is an anonymous story or story from ancient times that lived among the community and was passed down orally or from generation to generation as a suggestion to convey a message or mandate.